Mediation by NF-κB of cytokine induced expression of intercellular adhesion molecule 1 (ICAM-1) in an intestinal epithelial cell line, a process blocked by proteasome inhibitors. Issue 6 (1st June 1998) - Jobin, C; Hellerbrand, C; Licato, L L; Brenner, D A; Sartor, R B
Abstract : Background/aims —The gene promoter for the intercellular adhesion molecule ICAM-1 possesses binding sites for several transcriptional factors, including nuclear factor κB (NF-κB). The role of NF-κB in ICAM-1 gene regulation was therefore examined by using different proteasome inhibitors in tumour necrosis factor α (TNF-α) stimulated IEC-6 rat intestinal epithelial cells. Methods —ICAM-1 expression was analysed by enzyme linked immunosorbent assay (ELISA), reverse transcriptase polymerase chain reaction, and immunohistochemistry. Steady state levels of cytoplasmic IκB protein were evaluated by western blot, and nuclear translocation of NF-κB was determined by electrophoretic mobility shift assay and immunofluorescence staining. Cell adhesion was assayed by measuring the binding of fluorescence labelled MOLT-4 cells. Results —TNF-α induced ICAM-1 mRNA and protein expression in IEC-6 cells, which was followed by increased adhesion of MOLT-4 lymphocytes. Blocking TNF-α induced IκBα degradation with proteasome inhibitors reduced TNF-α induced NF-κB activation and ICAM-1 gene induction and notably decreased MOLT-4 cell adhesion without affecting Jun N-terminal kinase (JNK/SAPK) activity or de novo protein synthesis. Conclusion —TNF-α induction of ICAM-1 expression is mediated by the transcription factor NF-κB and can be inhibited by blocking IκBα degradation. Thus the IκB/NF-κB system is a promising target for pharmacological modulation of the expression of adhesion molecules and other inflammatory genes in the intestine.